Campaña de marketing digital para las redes sociales de Kametsa EIRL - Miranda Valdivia, Nicolas (2022)
This professional project will design a communication campaign for the return to operations of Kametsa E.I.R.L. It was closed due to the global pandemic caused by COVID-19 for the entirety of 2021 and reopened in March 2022. In addition to positioning Kametsa as one of the main nighttime tourist destinations in Junín, Perú; various traditional marketing tools and techniques will be integrated such as digital marketing too. From traditional marketing instruments, the campaign relied on the use of flyers and banners that were located at key points where they were exposed to the target audience. In terms of digital space, content marketing will be used through social media standards, which are square or 1:1 post and vertical or 9:16 stories and reels to achieve the spread of content and information.